2004
DOI: 10.1038/nature02839
|View full text |Cite|
|
Sign up to set email alerts
|

Complete photo-fragmentation of the deuterium molecule

Abstract: However, despite 80 years of theoretical attention, near exact calculations for such systems are only available for bound states. On the experimental side, the tests of these calculations are largely based upon level energies or single particle momentum 3 distributions. Very promising and challenging new classes of experiments are those which achieve a complete description of the outcome following the excitation of the ground state to an unbound continuum. The momenta, i.e. the set of vectors, of all the fragm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
134
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 152 publications
(143 citation statements)
references
References 28 publications
8
134
0
1
Order By: Relevance
“…In the indirect process (sometimes also referred to as a sequential process), photoejection of one electron leads to an intermediate cation state, which later decays by autoionization or other processes (e.g., Auger decay, fluorescence, etc.). After a couple of decades of studying the PDI of simple atoms and diatomic molecules (e.g., He, H 2 , N 2 , CO) in great detail [2][3][4][5][6][7][8][9][10], the investigation has been extended to polyatomic molecules in order to gain a general understanding of the double-ionization process in more complex systems. Simple hydrocarbon molecules are an ideal testbed for a series of studies with increasing complexity.…”
Section: Introductionmentioning
confidence: 99%
“…In the indirect process (sometimes also referred to as a sequential process), photoejection of one electron leads to an intermediate cation state, which later decays by autoionization or other processes (e.g., Auger decay, fluorescence, etc.). After a couple of decades of studying the PDI of simple atoms and diatomic molecules (e.g., He, H 2 , N 2 , CO) in great detail [2][3][4][5][6][7][8][9][10], the investigation has been extended to polyatomic molecules in order to gain a general understanding of the double-ionization process in more complex systems. Simple hydrocarbon molecules are an ideal testbed for a series of studies with increasing complexity.…”
Section: Introductionmentioning
confidence: 99%
“…Recent experimental investigations have focused on double photoionization (DPI) of two-electron atoms [1][2][3][4][5][6][7] and molecules [8][9][10][11] as a sensitive probe of the correlated motion of electrons. The DPI problem is interesting from both experimental and theoretical viewpoints because the process by which an atom or molecule absorbs a photon of sufficient energy to eject two electrons into the continuum necessarily depends on electron correlation.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments in which both electrons are ejected from an oriented hydrogen molecule by absorption of a single photon are currently available [9,[71][72][73]. Among the latter, Weber et al [9,72] have recently demonstrated that the ejection pattern of the electrons depends sensitively on the bond distance between the two nuclei as they vibrate in their ground state.…”
Section: Double Photoionization Of Hmentioning
confidence: 99%
“…Among the latter, Weber et al [9,72] have recently demonstrated that the ejection pattern of the electrons depends sensitively on the bond distance between the two nuclei as they vibrate in their ground state. In the experiments, linearly polarized 75 eV synchrotron radiation was used to study single-photon induced fragmentation of molecular deuterium.…”
Section: Double Photoionization Of Hmentioning
confidence: 99%
See 1 more Smart Citation